Women's empowerment and social Justice in India (with special reference to U.P.) - Dhar, T.N. (2014)
In spite of different acts and schemes of government to empower the women in the country, they are discriminated and marginalised at every level of the society, whether it is social participation, political participation, economic participation, access to education and also reproductive healthcare. Women empowerment cannot be possible unless women come with and help to self-empower themselves. There is a need to formulate reducing feminised poverty, promoting education and prevention and elimination of violence against women. - Reproduced.
Keywords: Social justice; Women